Arbitraż inwestycyjny w stosunkach polsko-ukraińskich - Rodziewicz, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Main aim of this article is presentation of the legal framework for international investment arbitration in Polish — Ukrainian relations. Article presents the provisions of bilateral agreement on promotion and protection of foreign investment between the two mentioned countries, as well as the provisions of multilateral international agreement to which both Poland and Ukraine are parties, namely the Energy Charter Treaty. Considerations in the article relate primarily to the legal framework of investment arbitration, however, also addresses the question of an economic nature which are tied to the protection and promotion of foreign investment. Some observations made in the article are more universal, not only referring to the investment arbitration in the Polish — Ukrainian relations but also retain their validity in relation to any investment disputes between the Polish and other countries, or states parties to the European Energy Charter.
Keywords: Polska; Ukraina; stosunki polsko-ukraińskie; arbitraż inwestycyjny